Comparative evaluation of cocoa seeds germination in local variety Gantarangkeke Bantaeng (GTB) with MCC 01 variety using seed priming treatment. Issue 4 (July 2021) - Hardiansyah, M Y; Amas, A N K; Musa, Y; Jaya, A M
Abstract: Gantarangkeke Bantaeng (GTB) variety seed is a type of local seed that has experienced a decline in its existence due to the emergence of superior seed types such as the MCC 01 variety resulting in low local cocoa production due to the lack of use of GTB seeds in South Sulawesi. One of the causes of low seeds capability is the lack of special treatment given to seeds which refers to the inhibition of germination of cultivated cocoa seeds. Seed priming is a treatment of soaking seeds with microbes to improve the quality of seeds germination. This study aims to compare the germination of local varieties of cocoa seeds GTB with varieties MCC 01 using Plant Growth Promoting Rhizobacteria (PGPR) seed priming treatment. This study employed a randomized block design (RBD). Two cocoa seed varieties used as the first factor consisted of local GTB and MCC 01, while the seed priming treatment as the second factor consisted of PGPR concentrations of 0% (control), 5%, 10%, and 15%. The results indicate that the seed priming treatment affected the germination of two cocoa varieties seeds which included the parameters of MCC 01 seeds germination and the growth speed which was higher than local GTB seeds, 100.00% and 7.14%/etmal, respectively. Abnormal seedlings in local GTB variety were higher than MCC 01 seeds (10.00%). It can be concluded that the seed priming treatment of cocoa seeds has a high effect on seed germination of the MCC 01 variety compared to the local variety GTB.